Programa de salud ocupacional para la prevención de riesgos biológicos de los profesionales que laboran en el servicio de hospitalización del Hospital Pediátrico Alfonso Villagómez Román de la ciudad de Riobamba - Londo Auquilla, Dora Alexandra (2017)
The present investigation has been carried out in response to staff working in the hospitalization service area absenteeism due to diseases of biological origin, which was presented as a line or diagnostic investigation. The result showed absenteeism of 43 working days from January to May 2016 and the consequences implied for both, the worker and the institution. For these considerations, the following general objective is proposed: To carry out the occupational health program for the prevention of biological risks of the professionals who work in the hospitalization service of “Alfonso Villagómez Román Pediatric Hospital” of Riobamba city. The theoretical framework details the contents that involve the topic: biological risk factors and possible contagion by any of the ways of entry that are known. The research is non-experimental design, application type and longitudinal since it stated a thesis with posed solutions to the problems. The entire population working in the hospitalization service was investigated, it ist, Medical Doctors, General Practitioners, Nursing Graduates, Nursing Assistants and Backpacker. Deductive research method and the primary technique observation were used. A survey and collection of samples prior to the completion of the occupational health program were carried used out. The verification of the general hypothesis was based on the verification of the specific hypothesis with its results and statistically Chi square was used. The research hypothesis was carried out with a significant decrease in days of work absenteeism in the period between January and May of 2017 unlike the same period in 2016. Conclusions according to the results and experiences obtained in the present investigation were obtained and respective recommendations were set.